The association between perception of esthetic and oral hygiene practice: A cross sectional study among Saudi adolescent - Jafer Albohassan; Ali Almaydani; Abdulqader Alhammadi; Abdulaziz Almurayhil (Elsevier, 2019)
Aim: To study The Association between Perception of Aesthetics and Oral Hygiene Practices. Methods: Data was collected using a questionnaire. The questionnaire was distributed among middle school adolescent for both genders in eastern region in Saudi Arabia. Result: The average score of esthetic perception among adolescents was 31.44 with SD of (5.092). The oral hygiene for the adolescents was determined by brushing frequency and the use of fluoridated tooth paste. Regarding brushing frequency, the study showed that half of the adolescents 836 (51%) brushed their teeth twice daily, 455 (27.8%) brushed once daily, 155 (9.5%) brushed 1-2 times weekly, 55 (3.4%) brushed more than once monthly and those who didn't brush their teeth were 137 (8.4%). Conclusion: There was a statistically significant relationship between oral hygiene and esthetics perception.